A local mesh replacement method for modeling near-interfacial crack growth in 2D composite structures. (February 2015) - Wang, Zhiyong; Yu, Hongjun; Wang, Zhihua
Highlights: A local mesh replacement method based on the XFEM is developed. The numerical method is verified by several benchmark problems. The method ensures the computational accuracy and efficiency simultaneously. The method shows good ability for near-interfacial crack growth modeling. Abstract: An extended-finite-element-based method is proposed to accommodate the arbitrary motion of a crack in a general two-dimensional domain containing different kinds of material interfaces. To obtain the accurate stress intensity factors (SIFs) when the crack tip approaches the interface, the interpolation method in the vicinity of the crack tip employed in the extended finite element method (XFEM) is replaced with one that is derived from a moving mesh patch. Mesh configurations in this patch are the same as that adopted in the finite element method (FEM) for crack problems. The boundary of the patch is required to be coincident with background-mesh element edges and only the patch mesh works during the computation. As a result, the major advantages of the XFEM for modeling crack growth are preserved. The simulations are accomplished using a new domain expression of an interaction integral for evaluating stress intensity factors, and the maximum hoop stress criterion for crack-growth direction prediction. Several numerical examples are presented to prove the capability and practicability of the proposed technique and the program.